2022
DOI: 10.3389/fonc.2022.856974
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Stem-Like Cells in Drug Resistance: A Review of Mechanisms and Novel Therapeutic Strategies to Overcome Drug Resistance

Abstract: Breast cancer is the most frequent type of malignancy in women worldwide, and drug resistance to the available systemic therapies remains a major challenge. At the molecular level, breast cancer is heterogeneous, where the cancer-initiating stem-like cells (bCSCs) comprise a small yet distinct population of cells within the tumor microenvironment (TME) that can differentiate into cells of multiple lineages, displaying varying degrees of cellular differentiation, enhanced metastatic potential, invasiveness, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 317 publications
0
31
0
Order By: Relevance
“…Patients with human epidermal growth factor 2 (HER2)-positive advanced breast cancer expected a median PFS of 18.5 months in the era of HER2-targeted agents trastuzumab and pertuzumab [9,10]. However, immunotherapy and targeted therapy were greatly limited by low response rates, lack of effective response predictors, resistance as well as drug toxicity [11][12][13]. In this context, therapies which could induce alternate forms of regulated cell death, ferroptosis, pyroptosis, necroptosis and apoptosis, for instance, become potential strategies to eliminate resistant breast cancer cells and improve survival [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with human epidermal growth factor 2 (HER2)-positive advanced breast cancer expected a median PFS of 18.5 months in the era of HER2-targeted agents trastuzumab and pertuzumab [9,10]. However, immunotherapy and targeted therapy were greatly limited by low response rates, lack of effective response predictors, resistance as well as drug toxicity [11][12][13]. In this context, therapies which could induce alternate forms of regulated cell death, ferroptosis, pyroptosis, necroptosis and apoptosis, for instance, become potential strategies to eliminate resistant breast cancer cells and improve survival [11].…”
mentioning
confidence: 99%
“…However, immunotherapy and targeted therapy were greatly limited by low response rates, lack of effective response predictors, resistance as well as drug toxicity [11][12][13]. In this context, therapies which could induce alternate forms of regulated cell death, ferroptosis, pyroptosis, necroptosis and apoptosis, for instance, become potential strategies to eliminate resistant breast cancer cells and improve survival [11].…”
mentioning
confidence: 99%
“…As a traditional cancer treatment modality, chemotherapy alone can inhibit tumor growth to a certain extent [ 51 ]. However, most chemotherapeutic agents have suboptimal accumulation barriers [ 52 ]; these severely impede clinical treatment when combined with tumor resistance [ 5 , 51 ]. We designed a graded targeting multifunctional system that significantly improved drug enrichment in tumor tissues through primary targeting, solving the above-mentioned limitations effectively.…”
Section: Resultsmentioning
confidence: 99%
“…However, the enrichment rate of drugs or contrast agents in the target region is poor owing to the complex environment of the human body [ 4 ], which makes it impossible to diagnose and treat tumors efficiently at the molecular level. The low drug enrichment rate and high drug resistance of tumor cells, especially the high drug resistance of cancer stem cells (CSCs), also decrease the efficiency of the clinical drug treatment [ 5 , 6 ]. Recently, targeted drug delivery has gained attention as an effective strategy for precision therapy [ [7] , [8] , [9] ].…”
Section: Introductionmentioning
confidence: 99%
“…CSCs have been recognized as the main cause of drug resistance, metastasis, and recurrence of cancer (166,167). Growing evidence suggests that miRNAs are involved in cancer drug resistance by altering the characteristics of CSCs (168). For instance, Zhang et al found that miR-132 was upregulated in the Lrg5 + gastric CSCs isolated from MKN45 and MKN28 cells.…”
Section: Mirnas Alter Stemness Characteristics and Emt In Cancer Cellsmentioning
confidence: 99%